The origin of graphite morphology in cast iron. (March 2022) - Tewary, Ujjal; Paul, Dennis; Mehtani, H.K.; Bhagavath, Shishira; Alankar, Alankar; Mohapatra, Goutam; Sahay, Satyam S.; Panwar, Ajay S.; Karagadde, Shyamprasad; Samajdar, Indradev
Abstract: Applications of cast irons, from mundane to more challenging, are decided by the morphology of free graphite in the metallic matrix. The morphology changes from flake to spheroidal, as controlled by magnesium (Mg) addition during metal castings. Though this technology dates back several decades, the exact mechanism remains debatable. This study used a combination of industrial casting trials, analytical microscopy, and molecular dynamics (MD) simulations to address this question. It was experimentally established that the shape change was accompanied by a change in the growth direction, from prism to basal in the graphite, and atomic segregation of Mg at the interface. MD simulations indicated a combination of migration of oxygen (O) atoms and Mg-O interactions, respectively in the prism and basal oriented graphite, resulted in cross-over in interfacial free energy with Mg concentration. The anisotropic growth by high energy interface, controlled by interface chemistry, thus defined the mechanistic origin for the graphite morphology in cast iron. Graphical abstract: Image, graphical abstract